A method for inducing and regulating crystallization of zinc-aluminum hydrotalcite by using zif-8 seed and application thereof
Patent Information
- Application Number
- CN202610253556.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-03
- Publication Date
- 2026-10-27
AI Technical Summary
1、本发明首创性地将ZIF-8纳米晶作为牺牲性晶种引入合成体系,通过异相成核机制精准控制水滑石结晶过程,有效抑制了LDH的均相无序成核,成功制得粒径800-900nm、分布均匀的类球状锌铝水滑石,实现了对晶体生长过程的精准调控,工艺流程简单,适用于工业化生产,显著优于传统方法。
Smart Images

Figure CN122977430A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic functional material preparation technology, and in particular to a method and application of inducing and controlling the crystallization of zinc-aluminum hydrotalcite using ZIF-8 seed crystals. Background Technology
[0002] Polyvinyl chloride (PVC), as one of the world's largest-produced general-purpose plastics, is widely used in building materials, packaging films, outdoor furniture, and other fields due to its excellent mechanical properties, chemical resistance, and cost advantages. However, the unstable chlorine and tertiary carbon atoms in the PVC molecular chain make it highly susceptible to a chain degradation reaction of dehydrochlorination under long-term heat, oxygen, and especially ultraviolet radiation. This leads to severe yellowing, embrittlement, and loss of mechanical properties, greatly shortening the service life of the products.
[0003] To mitigate aging issues, industry often relies on organic UV absorbers such as benzotriazoles. While these small molecules offer significant initial protection, they suffer from inherent defects such as easy migration, volatility, and extraction, making it difficult to meet the long-term durability requirements of high-end products. In recent years, inorganic layered materials—zinc-aluminum hydrotalcite (ZnAl-LDH)—have shown great application potential due to their unique layered structure: the zinc component in its layers possesses intrinsic UV shielding capabilities, while the interlayer anions can effectively capture and neutralize hydrogen chloride generated during degradation, fundamentally inhibiting autocatalytic degradation and achieving multi-layered protection against UV, heat, and acid. However, ZnAl-LDH nanosheets prepared by traditional co-precipitation methods exhibit a severe tendency to aggregate, and their wide and difficult-to-control crystal size distribution leads to poor dispersibility in polymer matrices, not only creating stress defects but also significantly reducing the transparency of products due to light scattering effects, thus hindering their application in high-end transparent / semi-transparent PVC.
[0004] Some studies have found that LDH growth can be effectively controlled by pre-preparing LDH nanocrystal seeds and then using a secondary growth method. For example, films grown by secondary growth on a nickel mesh loaded with a Ni-Al-LDH seed layer have higher crystallinity and uniformity than films grown in situ under the same hydrothermal conditions on a seedless substrate (Zhang F, Guo L, Xu S, et al. Preparation of nickel–aluminum-containing layered double hydroxide films by secondary (seeded) growth method and their electrochemical properties. Langmuir, 2015, 31(24): 6704-6712.). Other studies have shown that the addition of seeds can promote crystal growth and aggregation, control the formation of dense bulk LDH, reduce its porosity and pore size, and enhance the ability of LDH to adsorb and remove arsenic (Shi, Miao, et al. "ZnFe-LDH synthesized by seed-induced method to simultaneousenhance arsenic removal, stabilization and sludge reduction"). Journal of Hazardous Materials 480 (2024): 136459.); and the tunable growth of layered double hydroxide nanosheets through hydrothermal conversion of atomic layer deposition seed layers (Ortiz-Ortiz, Alondra M., et al. "Tunable growth of layered double hydroxide nanosheets through hydrothermal conversion of atomic layer deposition seed layers."). Chemistry of Materials 36.17 (2024):8300-8310). However, these are all extensions based on the same type of hydrotalcite, and the resulting products are all nanosheets with lateral dimensions much larger than longitudinal dimensions.
[0005] On the other hand, metal-organic frameworks (MOFs) are often used as templates for heterogeneous nucleation due to their highly ordered pore structure and controllable composition. ZIF-8 (Zeolitic Imidazolate Framework-8) is a Zn-based MOF, whose Zn... 2+It forms a stable Zn-N tetrahedral framework with imidazole ligands, exhibiting excellent chemical stability and high specific surface area. Zn in ZIF-8 2+ Zn in ZnAl-LDH 2+ It exhibits good chemical compatibility. Previous studies have shown that ZIF-8 can be grown on the surface of magnesium aluminum layered double hydroxide (MgAl-LDH@ZIF-8composites by in situ growth method for highly efficient phosphate removal. New Journal of Chemistry, 2022, 46(38): 18295-18305.), indicating that the two crystal lattices are compatible. If ZIF-8 is used as a seed crystal, it is expected to induce the ordered growth of ZnAl-LDH using ZIF-8 as the nucleus, thereby avoiding the disordered generation of homogeneous LDH nuclei and achieving precise control of crystal size and morphology. Simultaneously, because ZIF-8 is less stable than LDH, by controlling the conditions, it is expected to achieve the transformation of ZIF-8 to ZnAl-LDH during LDH growth, avoiding the presence of impurities in the product. Against this backdrop, this invention proposes an innovative strategy for inducing the growth of ZnAl-LDH with uniform size and excellent dispersion by using metal-organic framework ZIF-8 as a seed crystal. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of traditional zinc-aluminum hydrotalcite (ZALT), such as easy agglomeration, uneven size, and poor transparency in application, and to provide a method and application for inducing the growth of uniformly sized ZALT using ZIF-8 seed crystals. This method, through precise control of the crystallization process, yields highly dispersible hydrotalcite products for the preparation of high-transparency, long-lasting anti-aging high-end PVC composite materials.
[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing zinc-aluminum hydrotalcite, comprising the following steps: Step 1: Preparation of ZIF-8 seed crystal suspension: (a) Zinc nitrate solution and 2-methylimidazole solution were mixed and stirred vigorously to induce rapid nucleation, followed by static aging to complete crystal growth; (b) Mix the crystals from step (a) with water to obtain a ZIF-8 seed suspension; Step 2: Prepare the LDH precursor solution: (c) Zinc nitrate, aluminum nitrate and water are mixed to obtain solution A; (d) Mix the precipitant, carbon source, and water to obtain solution B; Step 3: Co-precipitation and hydrothermal crystallization: (e) Under a protective gas environment, solutions A and B are simultaneously and slowly added dropwise to the ZIF-8 seed suspension, and the pH of the entire system is controlled at 7.5~8.5. After the addition is completed, the mixture is stirred continuously to carry out one reaction to complete the induced nucleation of the ZIF-8 surface. (f) After the first reaction in step (e) is completed, the pH is adjusted to 10.5~11.5 to carry out a second reaction, so as to complete the growth of LDH and the conversion and removal of ZIF-8, and obtain slurry; Step 4: Product post-processing: (g) After cooling the slurry, centrifuge, wash and dry it in sequence to obtain the zinc-aluminum hydrotalcite.
[0008] Preferably, in step (a), the mass-to-volume ratio of zinc nitrate hexahydrate to water in the zinc nitrate solution is 10-15 g: 70-90 mL; In step (a), the mass-to-volume ratio of 2-methylimidazole to water in the 2-methylimidazole solution is 200-240 g: 700-900 mL; In step (a), the volume ratio of zinc nitrate solution to 2-methylimidazole solution is 1:8~12; In step (a), the stirring temperature is room temperature, the stirring time is 3-7 minutes, and the stirring speed is 500-1500 rpm. In step (a), the aging temperature is room temperature, and the aging time is 1.5 to 3 hours.
[0009] Preferably, the concentration of the ZIF-8 seed suspension in step (b) is 1~3 mg / L.
[0010] Preferably, in step (c), the molar ratio of zinc nitrate to aluminum nitrate is 1 to 3:1, and the metal ion concentration of solution A is 0.05 to 0.2 mol / L.
[0011] Preferably, in step (d), the precipitant is urea, and the carbon source is one or more of ammonium carbonate and sodium carbonate; In step (d), the molar volume ratio of precipitant, carbon source and water is 10~20 mmol: 2~5 mmol: 40~60 mL.
[0012] Preferably, the protective gas in step (e) is nitrogen; The dripping rate in step (e) is 1~2 mL / min; In step (e), the volume ratio of solution A to solution B is 1:1; In step (e), the temperature of the reaction is 75~85℃ and the reaction time is 2h.
[0013] Preferably, the temperature of the secondary reaction in step (f) is 75~85℃, and the time of the secondary reaction is 2~22h.
[0014] Preferably, the drying temperature in step (g) is 60~80℃ and the drying time is 10~16h.
[0015] The present invention also provides a method for preparing zinc-aluminum hydrotalcite and the zinc-aluminum hydrotalcite obtained therefrom.
[0016] This invention also provides an application of zinc-aluminum hydrotalcite in the preparation of polyvinyl chloride composite materials.
[0017] The present invention has the following beneficial effects: 1. This invention innovatively introduces ZIF-8 nanocrystals as sacrificial seed crystals into the synthesis system, and precisely controls the crystallization process of hydrotalcite through a heterogeneous nucleation mechanism, effectively suppressing the homogeneous disordered nucleation of LDH, and successfully producing spherical zinc-aluminum hydrotalcite with a particle size of 800-900nm and uniform distribution. It achieves precise control of the crystal growth process, has a simple process flow, is suitable for industrial production, and is significantly superior to traditional methods.
[0018] 2. The ZnAl-LDH product prepared by this invention has excellent dispersibility in polyvinyl chloride matrix. While imparting excellent thermal stability and HCl absorption capacity to the material, it perfectly maintains the high transparency of the product, providing a new long-term and stable anti-aging solution for high-end PVC products.
[0019] 3. The ZnAl-LDH prepared in this invention has both UV shielding and HCl capture functions, which can significantly delay the degradation process of PVC under the action of heat, light, and oxygen. Experiments show that after 1000 hours of QUV aging, the yellowness index of the PVC composite material with added LDH changes significantly less than that of the control group of traditional LDH and organic UV absorbers, and the light transmittance retention rate is as high as 94% or more. Attached Figure Description
[0020] Figure 1 Here is a scanning electron microscope image of the ZIF-8 seed crystal in Example 1; Figure 2 The image shown is a scanning electron microscope image of ZnAl-LDH obtained in Example 2. Figure 3 The image shows a scanning electron microscope (SEM) image of ZnAl-LDH obtained in Comparative Example 1. Detailed Implementation
[0021] This invention provides a method for preparing zinc-aluminum hydrotalcite, comprising the following steps: Step 1: Preparation of ZIF-8 seed crystal suspension: (a) Zinc nitrate solution and 2-methylimidazole solution were mixed and stirred vigorously to induce rapid nucleation, followed by static aging to complete crystal growth; (b) Mix the crystals from step (a) with water to obtain a ZIF-8 seed suspension; Step 2: Prepare the LDH precursor solution: (c) Zinc nitrate, aluminum nitrate and water are mixed to obtain solution A; (d) Mix the precipitant, carbon source, and water to obtain solution B; Step 3: Co-precipitation and hydrothermal crystallization: (e) Under a protective gas environment, solutions A and B are simultaneously and slowly added dropwise to the ZIF-8 seed suspension, and the pH of the entire system is controlled at 7.5~8.5. After the addition is completed, the mixture is stirred continuously to carry out one reaction to complete the induced nucleation of the ZIF-8 surface. (f) After the first reaction in step (e) is completed, the pH is adjusted to 10.5~11.5 to carry out a second reaction, so as to complete the growth of LDH and the conversion and removal of ZIF-8, and obtain slurry; Step 4: Product post-processing: (g) After cooling the slurry, centrifuge, wash and dry it in sequence to obtain the zinc-aluminum hydrotalcite.
[0022] In this invention, the preferred mass-to-volume ratio of zinc nitrate hexahydrate to water in the zinc nitrate solution in step (a) is 10-15g:70-90mL, more preferably 11-14g:72-88mL, and even more preferably 11-13g:75-85mL.
[0023] In this invention, the mass-to-volume ratio of 2-methylimidazole to water in the 2-methylimidazole solution in step (a) is preferably 200-240g:700-900mL, more preferably 205-235g:720-880mL, and even more preferably 210-230g:750-850mL.
[0024] In this invention, the volume ratio of zinc nitrate solution to 2-methylimidazole solution in step (a) is preferably 1:8 to 12, more preferably 1:9 to 11, and even more preferably 1:10.
[0025] In this invention, the stirring temperature in step (a) is preferably room temperature.
[0026] In this invention, the stirring time is preferably 3 to 7 minutes, more preferably 4 to 6 minutes, and even more preferably 5 minutes.
[0027] In this invention, the stirring rate is preferably 500-1500 rpm, more preferably 800-1200 rpm, and even more preferably 1000 rpm.
[0028] In this invention, the aging temperature in step (a) is preferably room temperature.
[0029] In this invention, the aging time is preferably 1.5 to 3 hours, more preferably 2 to 2.5 hours, and even more preferably 2 hours.
[0030] In this invention, the crystals obtained in step (a) are centrifuged and washed with water, and then mixed with water to obtain a ZIF-8 seed suspension.
[0031] In this invention, the seeds in the ZIF-8 seed suspension are ZIF-8 nano-seeds, and the particle size of the ZIF-8 nano-seeds is 20~150nm.
[0032] In this invention, the concentration of the ZIF-8 seed suspension in step (b) is preferably 1~3 mg / L, more preferably 1.2~2.8 mg / L, and even more preferably 1.5~2.5 mg / L.
[0033] In this invention, the molar ratio of zinc nitrate to aluminum nitrate in step (c) is preferably 1 to 3:1, more preferably 1.5 to 2.5:1, and even more preferably 2:1.
[0034] In this invention, the metal ion concentration of solution A is preferably 0.05~0.2 mol / L, more preferably 0.08~0.17 mol / L, and even more preferably 0.1~0.15 mol / L.
[0035] In this invention, the precipitant in step (d) is preferably urea, and the carbon source is preferably one or more of ammonium carbonate and sodium carbonate.
[0036] In this invention, the molar volume ratio of precipitant, carbon source and water in step (d) is 10~20mmol:2~5mmol:40~60mL, more preferably 12~18mmol:2.5~4.5mmol:45~55mL, and even more preferably 15mmol:3mmol:50mL.
[0037] Preferably, the protective gas in step (e) is nitrogen.
[0038] In this invention, the dripping rate in step (e) is preferably 1 to 2 mL / min, more preferably 1 to 1.5 mL / min, and even more preferably 1 mL / min.
[0039] In this invention, the volume ratio of solution A to solution B in step (e) is preferably 1:1.
[0040] In this invention, the temperature of the primary reaction in step (e) is preferably 75~85°C, more preferably 77~83°C, and even more preferably 80°C.
[0041] In this invention, the reaction time is preferably 1 to 3 hours, more preferably 1.5 to 2.5 hours, and even more preferably 2 hours.
[0042] In this invention, the temperature of the secondary reaction in step (f) is preferably 75~85°C, more preferably 77~83°C, and even more preferably 80°C.
[0043] In this invention, the time for the secondary reaction is preferably 2 to 22 hours, more preferably 3 to 20 hours, and even more preferably 4 to 18 hours.
[0044] In step three of this invention, the pH of the system is adjusted by using a sodium hydroxide solution.
[0045] In this invention, the drying temperature in step (g) is preferably 60~80°C, more preferably 65~75°C, and even more preferably 70°C.
[0046] In this invention, the drying time is preferably 10-16 hours, more preferably 11-15 hours, and even more preferably 12-14 hours.
[0047] In this invention, the zinc-aluminum hydrotalcite prepared in step (g) is a uniformly sized spherical or disc-shaped particle assembled from nanosheets, with a particle size distribution range of 800~900 nm and a size distribution deviation of less than ±20%.
[0048] The present invention also provides a method for preparing zinc-aluminum hydrotalcite and the zinc-aluminum hydrotalcite obtained therefrom.
[0049] This invention also provides an application of zinc-aluminum hydrotalcite in the preparation of polyvinyl chloride composite materials.
[0050] In this invention, the application method of the zinc-aluminum hydrotalcite in the preparation of polyvinyl chloride composite materials includes the following steps: The composite polyvinyl chloride material is prepared by mixing zinc-aluminum hydrotalcite, PVC resin, heat stabilizer and plasticizer at high speed, followed by double-roll melt blending and hot pressing.
[0051] In this invention, the mass ratio of zinc-aluminum hydrotalcite, PVC resin, heat stabilizer and plasticizer is 0.5 phr:100 phr:1.6 phr:40 phr, where phr represents "parts / hundred parts of resin".
[0052] In this invention, the preferred temperature for the two-roll melt blending is 180~220℃, and the preferred time for the two-roll melt blending is 15~30min.
[0053] In this invention, the zinc-aluminum hydrotalcite serves as a multifunctional additive, forming a stable interface with the polymer matrix through its nanoscale dispersion characteristics.
[0054] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention. Example 1
[0055] Preparation of ZnAl-LDH by low addition of ZIF-8 seed crystals: 11.7 g of zinc nitrate hexahydrate was dissolved in 80 mL of water to obtain a zinc nitrate solution, and 227.0 g of 2-methylimidazole was dissolved in 800 mL of water to obtain a 2-methylimidazole solution. The zinc nitrate solution was then rapidly poured into the 2-methylimidazole solution (the volume ratio of zinc nitrate solution to 2-methylimidazole solution was 1:10), and the mixture was vigorously stirred at 1000 rpm for 5 minutes at room temperature. After centrifugation and washing five times with deionized water, the mixture was dispersed in water to prepare a ZIF-8 seed suspension with a concentration of 2 mg / mL.
[0056] Take 10 mL of seed crystal suspension (containing 0.02 g ZIF-8) and place it in a three-necked flask. Dissolve 4 mmol Zn(NO3)2·6H2O and 2 mmol Al(NO3)3·9H2O in 50 mL of water to prepare solution A (where the metal ion concentration of solution A is 0.12 mol / L, and the molar ratio of zinc nitrate to aluminum nitrate is 2:1); dissolve 15 mmol urea and 3 mmol Na2CO3 in 50 mL of water to prepare solution B. Under N2 protection and an 80℃ water bath, simultaneously add solutions A and B dropwise to the seed crystal suspension at a rate of 1 mL / min, maintaining the pH at 8.0 with a trace amount of sodium hydroxide solution, and carry out the first reaction for 2 hours to complete the induced nucleation of ZIF-8 surface while inhibiting homogeneous nucleation. Then adjust the pH to 10.0 with sodium hydroxide solution and continue the second reaction for 4 hours to obtain a slurry, completing the growth of LDH and the conversion and removal of ZIF-8. After cooling, the slurry is centrifuged and washed three times each with water and ethanol to thoroughly remove byproduct salts and any remaining organic ligands. Then, it is vacuum dried at 70°C for 12 hours and ground to obtain white ZnAl-LDH powder, which is zinc aluminum hydrotalcite.
[0057] 0.5 phr (parts / hundred parts of resin) of ZnAl-LDH was mixed with 100 phr of PVC resin, 1.6 phr of heat stabilizer and 40 phr of DOP plasticizer at high speed, and then stirred in a high-speed mixer (28000 rad / min) for 30 seconds. After natural cooling, the mixture was poured out and plasticized in a two-roll mill for 20 minutes (190℃, 15 / 20 rad / min). The mixture was then hot-pressed to obtain PVC sheets with a thickness of 0.5 mm.
[0058] Figure 1 This is a scanning electron microscope (SEM) image of the ZIF-8 seed crystal in this embodiment. Figure 1 It can be seen that the ZIF-8 seed crystals are uniform, with a particle size of 80±10 nm and high morphological consistency. Example 2
[0059] Preparation of ZnAl-LDH induced by adding ZIF-8 seed crystals: 11.7 g of zinc nitrate hexahydrate was dissolved in 80 mL of water to obtain a zinc nitrate solution, and 227.0 g of 2-methylimidazole was dissolved in 800 mL of water to obtain a 2-methylimidazole solution. The zinc nitrate solution was then rapidly poured into the 2-methylimidazole solution (the volume ratio of zinc nitrate solution to 2-methylimidazole solution was 1:10), and the mixture was vigorously stirred at 1000 rpm for 5 minutes at room temperature. After centrifugation and washing five times with deionized water, the mixture was dispersed in water to prepare a ZIF-8 seed suspension with a concentration of 2 mg / mL.
[0060] Take 50 mL of seed crystal suspension (containing 0.1 g ZIF-8) and place it in a three-necked flask. Dissolve 4 mmol Zn(NO3)2·6H2O and 2 mmol Al(NO3)3·9H2O in 50 mL of water to prepare solution A (where the metal ion concentration of solution A is 0.12 mol / L, and the molar ratio of zinc nitrate to aluminum nitrate is 2:1); dissolve 15 mmol urea and 3 mmol Na2CO3 in 50 mL of water to prepare solution B. Under N2 protection and an 80℃ water bath, simultaneously add solutions A and B dropwise to the seed crystal suspension at a rate of 1 mL / min, maintaining the pH at 8.0 with a trace amount of sodium hydroxide solution, and carry out the first reaction for 2 hours to complete the induced nucleation of ZIF-8 surface while inhibiting homogeneous nucleation. Then adjust the pH to 10.0 with sodium hydroxide solution and continue the second reaction for 4 hours to obtain a slurry, completing the growth of LDH and the conversion and removal of ZIF-8. After cooling, the slurry is centrifuged and washed three times each with water and ethanol to thoroughly remove byproduct salts and any remaining organic ligands. Then, it is vacuum dried at 70°C for 12 hours and ground to obtain white ZnAl-LDH powder, which is zinc aluminum hydrotalcite.
[0061] 0.5 phr (parts / hundred parts of resin) of ZnAl-LDH was mixed with 100 phr of PVC resin, 1.6 phr of heat stabilizer and 40 phr of DOP plasticizer at high speed, and then stirred in a high-speed mixer (28000 rad / min) for 30 seconds. After natural cooling, the mixture was poured out and plasticized in a two-roll mill for 20 minutes (190℃, 15 / 20 rad / min). The mixture was then hot-pressed to obtain PVC sheets with a thickness of 0.5 mm.
[0062] Figure 2 The image shown is a scanning electron microscope (SEM) image of ZnAl-LDH obtained in this embodiment. Figure 2 As can be seen from the data, the zinc-aluminum hydrotalcite particles obtained in this embodiment are uniform, with a particle size of 850±20 nm, high dispersibility, and a diameter-to-thickness ratio close to 1. Example 3
[0063] Preparation of ZnAl-LDH induced by high addition of ZIF-8 seed crystals: 11.7 g of zinc nitrate hexahydrate was dissolved in 80 mL of water to obtain a zinc nitrate solution, and 227.0 g of 2-methylimidazole was dissolved in 800 mL of water to obtain a 2-methylimidazole solution. The zinc nitrate solution was then rapidly poured into the 2-methylimidazole solution (the volume ratio of zinc nitrate solution to 2-methylimidazole solution was 1:10), and the mixture was vigorously stirred at 1000 rpm for 5 minutes at room temperature. After centrifugation and washing five times with deionized water, the mixture was dispersed in water to prepare a ZIF-8 seed suspension with a concentration of 2 mg / mL.
[0064] 200 mL of seed crystal suspension (containing 0.4 g ZIF-8) was placed in a three-necked flask. Solution A was prepared by dissolving 4 mmol Zn(NO3)2·6H2O and 2 mmol Al(NO3)3·9H2O in 50 mL of water (the metal ion concentration in solution A was 0.12 mol / L, and the molar ratio of zinc nitrate to aluminum nitrate was 2:1). Solution B was prepared by dissolving 15 mmol urea and 3 mmol Na2CO3 in 50 mL of water. Under N2 protection and in an 80℃ water bath, solutions A and B were simultaneously added dropwise to the seed crystal suspension at a rate of 1 mL / min. The pH was maintained at 8.0 with a trace amount of sodium hydroxide solution. The reaction was carried out for 2 hours to induce nucleation on the ZIF-8 surface while inhibiting homogeneous nucleation. The pH was then adjusted to 10.0 with sodium hydroxide solution, and a second reaction was carried out for 4 hours to obtain a slurry, completing the growth of LDH and the conversion and removal of ZIF-8. After cooling, the slurry is centrifuged and washed three times each with water and ethanol to thoroughly remove byproduct salts and any remaining organic ligands. Then, it is vacuum dried at 70°C for 12 hours and ground to obtain white ZnAl-LDH powder, which is zinc aluminum hydrotalcite.
[0065] 0.5 phr (parts / hundred parts of resin) of ZnAl-LDH was mixed with 100 phr of PVC resin, 1.6 phr of heat stabilizer and 40 phr of DOP plasticizer at high speed, and then stirred in a high-speed mixer (28000 rad / min) for 30 seconds. After natural cooling, the mixture was poured out and plasticized in a two-roll mill for 20 minutes (190℃, 15 / 20 rad / min). The mixture was then hot-pressed to obtain PVC sheets with a thickness of 0.5 mm. Comparative Example 1
[0066] Solution A was prepared by dissolving 4 mmol Zn(NO3)2·6H2O and 2 mmol Al(NO3)3·9H2O in 50 mL of water (the metal ion concentration in solution A was 0.12 mol / L, and the molar ratio of zinc nitrate to aluminum nitrate was 2:1). Solution B was prepared by dissolving 15 mmol urea and 3 mmol Na2CO3 in 50 mL of water. Under N2 protection and in an 80℃ water bath, solutions A and B were simultaneously added dropwise to the seed suspension at a rate of 1 mL / min. The pH was maintained at 8.0 with a trace amount of sodium hydroxide solution, and the reaction was carried out for 2 hours. Then, the pH was adjusted to 10.0 with sodium hydroxide solution, and the reaction was carried out for 4 hours to obtain a slurry. After cooling, the slurry was centrifuged, washed three times each with water and ethanol, and then vacuum dried at 70℃ for 12 hours. The slurry was then ground to obtain a white ZnAl-LDH powder, which is zinc aluminum hydrotalcite.
[0067] 0.5 phr (parts / hundred parts of resin) of ZnAl-LDH was mixed with 100 phr of PVC resin, 1.6 phr of heat stabilizer and 40 phr of DOP plasticizer at high speed, and then stirred in a high-speed mixer (28000 rad / min) for 30 seconds. After natural cooling, the mixture was poured out and plasticized in a two-roll mill for 20 minutes (190℃, 15 / 20 rad / min). The mixture was then hot-pressed to obtain PVC sheets with a thickness of 0.5 mm.
[0068] Figure 3 The image shown is a scanning electron microscope image of ZnAl-LDH obtained in this comparative example. Figure 3 It can be seen from the comparison that the zinc-aluminum hydrotalcite particles obtained in this example have large differences in size and exhibit many mixed crystal or multi-particle agglomeration phenomena. Comparative Example 2
[0069] PVC sheets were prepared using a commercially available benzotriazole UV absorber (UV-326) at an addition rate of 1.5 phr without the addition of any LDH, in the same manner as in Example 1. Comparative Example 3
[0070] Blank PVC sheets were prepared from PVC resin, heat stabilizer, and plasticizer without adding any UV stabilizer, using the same method as in Example 1.
[0071] ZIF-8 retention verification test in the product: Take 20 mg of the ZnAl-LDH powder product from Example 3 and disperse it in 1 mL of deuterated water. While stirring, blow dry hydrogen chloride gas into the solution to acidify the solution and degrade the product. After the powder is completely dissolved, perform a 1H nuclear magnetic resonance test. The result shows no H signal of 2-methylimidazole, indicating that there is no ZIF-8 residue in the obtained ZnAl-LDH powder product.
[0072] The performance of the ZnAl-LDH powder and PVC sheets obtained in each embodiment was tested, and the results are shown in Table 1: Table 1. Performance Comparison of ZnAl-LDH Powder and PVC Sheets Obtained in Each Example ; As shown in the above embodiments, this invention provides a method and application for the crystallization of zinc-aluminum hydrotalcite (LDH) induced and controlled by ZIF-8 seed crystals. The method for preparing ZIF-8 LDH includes the following steps: preparing a ZIF-8 seed crystal suspension; preparing an LDH precursor solution; co-precipitation and hydrothermal crystallization; and product post-treatment. This invention innovatively introduces ZIF-8 nanocrystals as sacrificial seed crystals into the synthesis system, precisely controlling the LDH crystallization process through a heterogeneous nucleation mechanism. This effectively suppresses the homogeneous disordered nucleation of LDH, successfully producing spherical ZIF-8 LDH with a uniform particle size of 800-900 nm. This achieves precise control of the crystal growth process, with a simple process flow suitable for industrial production, significantly superior to traditional methods. The ZnAl-LDH product prepared by this invention exhibits excellent dispersibility in vinyl PVC substrates, perfectly maintaining the high transparency of the product while imparting excellent thermal stability and HCl absorption capacity. This provides a long-lasting and stable anti-aging solution for high-end PVC products.
[0073] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing zinc-aluminum hydrotalcite, characterized in that, Includes the following steps: Step 1: Preparation of ZIF-8 seed crystal suspension: (a) Zinc nitrate solution and 2-methylimidazole solution were mixed and stirred vigorously to induce rapid nucleation, followed by static aging to complete crystal growth; (b) Mix the crystals from step (a) with water to obtain a ZIF-8 seed suspension; Step 2: Prepare the LDH precursor solution: (c) Zinc nitrate, aluminum nitrate and water are mixed to obtain solution A; (d) Mix the precipitant, carbon source, and water to obtain solution B; Step 3: Co-precipitation and hydrothermal crystallization: (e) Under a protective gas environment, solutions A and B are simultaneously and slowly added dropwise to the ZIF-8 seed suspension, and the pH of the entire system is controlled at 7.5~8.
5. After the addition is completed, the mixture is stirred continuously to carry out one reaction to complete the induced nucleation of the ZIF-8 surface. (f) After the first reaction in step (e) is completed, the pH is adjusted to 10.5~11.5 to carry out a second reaction, so as to complete the growth of LDH and the conversion and removal of ZIF-8, and obtain slurry; Step 4: Product post-processing: (g) After cooling the slurry, centrifuge, wash and dry it in sequence to obtain the zinc-aluminum hydrotalcite.
2. The method for preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that, In step (a), the mass-to-volume ratio of zinc nitrate hexahydrate to water in the zinc nitrate solution is 10-15 g: 70-90 mL; In step (a), the mass-to-volume ratio of 2-methylimidazole to water in the 2-methylimidazole solution is 200-240 g: 700-900 mL; In step (a), the volume ratio of zinc nitrate solution to 2-methylimidazole solution is 1:8~12; In step (a), the stirring temperature is room temperature, the stirring time is 3-7 minutes, and the stirring speed is 500-1500 rpm. In step (a), the aging temperature is room temperature, and the aging time is 1.5 to 3 hours.
3. The method for preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that, In step (b), the concentration of the ZIF-8 seed suspension is 1~3 mg / L.
4. The method for preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that, In step (c), the molar ratio of zinc nitrate to aluminum nitrate is 1 to 3:1, and the metal ion concentration of solution A is 0.05 to 0.2 mol / L.
5. The method for preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that, In step (d), the precipitant is urea, and the carbon source is one or more of ammonium carbonate and sodium carbonate. In step (d), the molar volume ratio of precipitant, carbon source and water is 10~20 mmol: 2~5 mmol: 40~60 mL.
6. The method for preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that, The protective gas in step (e) is nitrogen; The dripping rate in step (e) is 1~2 mL / min; In step (e), the volume ratio of solution A to solution B is 1:1; In step (e), the temperature of the reaction is 75~85℃ and the reaction time is 2h.
7. The method for preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that, The temperature of the secondary reaction in step (f) is 75~85℃, and the reaction time is 2~22h.
8. The method for preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that, In step (g), the drying temperature is 60~80℃ and the drying time is 10~16h.
9. A zinc-aluminum hydrotalcite prepared by the method of claim 1.
10. The application of the zinc-aluminum hydrotalcite of claim 9 in the preparation of polyvinyl chloride composite materials.